Professional Competence and Organizational Climate on Teacher Performance in Senior High Schools - Cucu Atikah; Hany Tutut Handayani; Sholih (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
Many teachers still exhibit suboptimal performance. The lack of human resources and issues related to insufficient facilities are also considered as factors hindering the improvement of teacher performance. Based on these issues, the objective of this research is to analyze the influence of professional competence and organizational climate on teacher performance in senior high schools. This study employs a quantitative method, emphasizing the collection of numerical data to be analyzed using statistical techniques. The population in this study consists of all teachers at a public high school, with a total of 46 teachers. The sample includes all teachers at the high school, also totaling 46 teachers, selected through the Total Sampling method. The data collection methods used include questionnaires and document studies. The research instrument comprises a structured closed-ended questionnaire and documentation guidelines. Data analysis techniques involve both descriptive and inferential statistical analysis. The results of the study reveal that professional competence has a positive and significant effect on teacher performance, with a coefficient value of 0.479. This indicates that improvements in professional competence will positively impact teacher performance. In addition, the organizational climate also significantly influences teacher performance, with a coefficient value of 0.580. If both professional competence and the school’s organizational climate are enhanced and well-conditioned, they will have a positive effect on improving teacher performance, which in turn will contribute to the improvement of educational quality.